2016
DOI: 10.1111/vsu.12508
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic, Surgeon and Owner Assessment of the BioMedtrix TATE®Elbow Arthroplasty

Abstract: A high complication rate and variability in component placement was recorded with TATE athroplasty. However, component malalignment did not negatively impact clinical outcome. Final clinical outcome was favorable for most cases with significant reductions in pain severity and interference scores despite no changes in mobility scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…, De Sousa et al . ) and has been used by the BVOA‐UoL Canine Hip Replacement Registry to assess postoperative outcomes (Forster et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…, De Sousa et al . ) and has been used by the BVOA‐UoL Canine Hip Replacement Registry to assess postoperative outcomes (Forster et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiological examination was performed by two independent observers (AN and NB) on two occasions 1 week apart. A protocol was followed to objectively measure component position, similar to that described by De Sousa and colleagues 17 and as illustrated in ►Fig. 5.…”
Section: Radiological Assessmentmentioning
confidence: 99%
“…Discontentment with this system clinically has resulted in the development of several new total or partial arthroplasty systems [13][14][15] one of which is the TATE elbow system, a semi-constrained cementless bi-component resurfacing implant; 16 a recent retrospective study evaluating this system showed good clinical results in a majority of cases, but with a high complication rate. 17 Protocols for evaluation of component placement following arthroplasty have been shown in both human beings and dogs to be important in predicting the success of surgery as well as the risk of complications occurring. [18][19][20][21][22][23][24] Preliminary retrospective evaluation of TATE elbow component positioning has been performed by De Sousa and colleagues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, very few peer‐review publications relate to this system. Function was subjectively evaluated as acceptable in 76% of clinical cases, although perioperative complications, most of them major, occurred in 60% of cases . This high rate of complications justifies efforts to identify prognostic variables influenced by the surgeon, including operative technique.…”
Section: Introductionmentioning
confidence: 99%